Effect of seed biopriming with liquid bacterial inoculants on quality of forage oats (Avena sativa) - VERMA, MEGHA; PANDOVE, GULAB; OBEROI, HARPREET KAUR; KAUR, SUKHDEEP; KALIA, ANU; SINGH, DEVINDER PAL; KAUR, JAGJOT (The Indian Journal of Agricultural Sciences, 2023)
The application of liquid bacterial inoculants along with the recommended dose of chemical fertilization improved the quality of forage oats at Bathinda and Ludhiana. The best quality attributes were observed with the treatment T11 (RDF + B. seminalis + S. maltophilia) with significant improvement in the crude protein (9.23 and 8.92%), ADF content (33.10 and 33.50%) and IVDMD (71.66 and 70.20%)at Bathinda and Ludhiana respectively. Further, correlation studies showed positive and significant correlation between ADF and NDF and the negative correlation with the rest of the quality attributes. Therefore, it is believed that liquid bacterial inoculants can play a significant role in ameliorating the forage oats quality, thus can help to enhance the overall animal productivity. In addition, potential of these liquid bacterial inoculants can be explored in integrated nutrient management or organic cultivation of forage oats as wellas in other crops.